Phylogenetic and taxonomic implications of protein variation in the Mesoamerican salamander genus Oedipina (Caudata: Plethodontidae) - Good, David A; Wake, David B (Revista de Biología Tropical, 1997)
An analysis of protein variation was conducted among 28 population samples of salamanders of .the genus Oedipina. collected in Guatemala, Honduras, Costa Rica, and Panama, in order to assess the validity oC currently recognized specles and to evaluate their phylogenetic relationships. A set oC eight species of the related genus Nototriton served as an outgroup. There are four major clades, with Nei geneuc distances between elades ranging frorn 0.46 to 2.67. Patteins of geographic variation within O.u.niformis as currently recognized indicate thatpopulations withinit should be placed ioto fourspecies: O. alfatoiis a valid species, and O. gracilis and O. pacificensis are